Economic impact of marine ecotourism on the local community in Semporna, Sabah, Malaysia - Rosmiza M.Z.; Nur Aqilah Hadifah Mohd Yusri; Fatin Umaira Muhamad Azian; Mohamad Syahrul Nizam Ibrahim; Mohamad Pirdaus Yusoh; Johan Johnes (Scopus, 2025)
The development of the tourism sector in a destination is heavily dependent on the existing natural resources, the patterns of supply, weather and seasonal influences, as well as current demand trends. The expansion of the tourism sector generates economic spillover benefits, thereby improving the welfare of the local population in a tourist destination. Consequently, this study focuses on the marine ecotourism destination in Semporna, Sabah, to assess the positive economic impact on the local community. A quantitative study was conducted with 80 respondents using purposive sampling methods. The findings reveal that marine ecotourism activities have had an economic impact on the local community, such as the expansion of employment and business opportunities, as well as the growth of small and medium-sized enterprises (SMEs). The growth of SMEs is predominantly within the food business sector, as well as businesses based on environmental and cultural products, which have become important income sources for the community. This has elevated the economic status of the local community and led to a shift in the primary employment activities of the population, from fishing to secondary and tertiary economic sectors. Therefore, stakeholders should implement strategies aimed at fostering a more integrated and inclusive local economic development, which involves active participation from the local community. Active community involvement, alongside stakeholder engagement, will ensure that the marine ecotourism sector remains relevant in enhancing economic benefits and supporting sustainable tourism development.